Upper trapezius fatigue in carpet weaving: the impact of a repetitive task cycle. Issue 1 (2nd January 2018) - Mahdavi, Neda; Motamedzade, Majid; Jamshidi, Ali Ashraf; Darvishi, Ebrahim; Moghimbeygi, Abbas; Heidari Moghadam, Rashid
Abstract : Introduction . Shoulder disorders are one of the most prevalent musculoskeletal disorders among carpet weavers. The most important cause of these disorders is muscle fatigue. The aim of the present study is to investigate the effect of carpet weaving characteristics on upper trapezius (UTr) muscle fatigue during a task cycle. Method . In this cross-sectional study, 9 women and 3 men participated. During an 80-min cycle of carpet weaving, a times-series model was applied to assess electromyography amplitude and frequency changes. Result . According to the joint analysis of electromyogram spectrum and amplitude method, the participants experienced 0% force decrease, 0.9% recovery, 18% force increase and 72% fatigue in the left UTr. Furthermore, the rates of force decrease, recovery, force increase and fatigue in the right UTr were 18%, 18%, 18% and 45%, respectively. Fatigue in the right and the left UTr was reported to be the dominant state during one carpet weaving task cycle. Conclusion . Task cycle appears to have a significant impact on UTr fatigue in participants, and UTr fatigue can be considered a serious risk factor in shoulder musculoskeletal disorders. Hence, further studies should focus on better workstations and work–rest periods during various subtasks.